Knowledge acquisition on tenancy mix of shopping centres in Klang Valley / Amiza Hanum Amin Nudin - Amin Nudin, Amiza Hanum (2017)
Proper property management of a shopping centre is important. This involved tenant mix management which is vital to the success of a shopping centre in Malaysia. However, not many empirical research has investigated the actual knowledge needed and practised to manage tenant mix. The purpose of this study is to establish knowledge in shopping centre management focussing on tenancy mix through knowledge acquisition approach. This research was carried out using both quantitative and qualitative method. The use of mixed method provided a more in-depth feedback to clarify the findings and patterns emerged. A semi-structured interview known as the Repertory Grid (RepGrid) technique was used to with addition of a questionnaire. The data collected from questionnaires were analysed using Microsoft Excel and Idiogrid Version 2.4 software. Generalized Procrustes Analaysis (GPA) was used to analyze the various and different inputs gathered from the 12 participants. This study is able to identify the knowledge related to tenant mix and its relevancy in the success of a shopping centre. Further finding shows that tenant mix is an important element in the success of managing a shopping centre and some of the practices suggested are out of context and not applicable in Malaysia. The Repertory Grid method has proven the ability and suitability in eliciting knowledge from the experts in shopping centre management specifically in tenant mix. Overall, these findings combined can be used in developing a prototype knowledge based decision support which can contribute a rich pool of knowledge for the shopping centre management personnel to keep up with the evolving needs and demands of their job scopes.